Ocean conditions drive interannual variability in juvenile albacore tuna (Thunnus alalunga) muscle energy content in the California Current System - Catherine F. Nickels; Barbara A. Muhling; Elan J. Portner; Owyn E. Snodgrass; Heidi Dewar (PLoS ONE, 2025)
Juvenile albacore tuna (Thunnus alalunga) undertake long migrations across the North Pacific that they fuel by feeding in the California Current System (CCS) during the summer. The CCS is a highly dynamic system, which can lead to differences in foraging success that may be indicated by differences in body condition. Assessed through stomach content analysis, albacore diet composition by mean proportional weight showed high interannual variability including some years characterized by large increases in consumption of anchovy (2011 = 81%, 2017, 2022) and sardine (Sardinops sagax, 2022). We used a generalized additive model (GAM) to investigate the impact of albacore length, month of collection, diet composition, and environmental conditions on albacore muscle energy content. Two proxies for muscle energy content, the carbon to nitrogen ratio (C:N) and ash free dry weight (AFDW), were positively but weakly correlated. Albacore C:N increased with month, body size, and upwelling in the first half of the year, and decreased with increasing sea surface temperature. The mean energy density of prey and chlorophyll-a concentration were not important predictors of muscle energy content, indicating that albacore may be resilient to changes in prey composition and productivity. Sea surface temperature was the most important predictor of muscle energy content, which suggests that marine heat waves and projected future warming in the CCS may have detrimental effects on albacore body condition or the value of the CCS as a foraging habitat.